Unlocking Adoption: Revealing Gamification's Influence on Indonesian Consumer Intentions in E-Commerce. - Nuril Aulia Munawaroh; Agus Hermawan; Diana Ambarwati (Cita konsultindo, 2024)
The rapid expansion of e-commerce in Indonesia and the integration of gamification features to enhance user engagement. Gamification is a strategy used in various industries, including e-commerce, to influence user behavior and foster interaction between consumers and products. The study aims to investigate the influence of social motives on attitudes towards e-commerce applications in the context of gamification. The main objective is to fill a gap in the existing literature by examining the relationship between gamification features and user engagement in e-commerce platforms, specifically in terms of long-term desire to use the platform and participate in word-of-mouth communication. The study employed a quantitative survey questionnaire and collected data from Indonesian consumers using the snowball sampling method. The data was analyzed using partial least squares structural equation modeling (PLS-SEM), and the results indicated that network exposure significantly influences social influence, recognition, and reciprocal benefit. The study found that gamification features, such as rewards, challenges, points, and enjoyment, can enhance user engagement in e-commerce platforms.